Investigating Optimum SiO2 Nanolubrication During Turning of AISI 420 SS - Reddy, N. M. M.; Chaganti, P. K. (Engineering, Technology & Applied Science Research, 2019)
AISI 420 martensitic stainless steel is used for making gas and steam turbine blades, steel balls and medical instruments, due to its anti-corrosive properties. Turning of AISI 420 SS would be a worthy procedure specifically in manufacturing high surface finish parts. In this work, effort has been made to investigate the cooling and lubricating performance of SiO2 (silicon dioxide) nanoparticles at different weight concentrations of 0.1g, 0.5g and 1g mixed in a novel developed base fluid (synthetic). The performance of optimum SiO2 based cutting fluid is evaluated based on the turning process with output responses like surface finish and cutting temperature. Taguchi technique was used with standard L9(3**4) orthogonal array. The responses, surface roughness, and cutting temperature were analyzed using S/N (signal-to-noise) and ANOVA (analysis of variance). This analysis identifies the significant input parameter combination to obtain minimum surface roughness and temperature.